Penguatan Manajemen Keuangan dan Pembukuan Kelompok UMKN Tenun Gedogan untuk Pemberdayaan Ekonomi Perempuan di Desa Pringgasela, Lombok Timur - M. Yusuf; Sab’ul Masani; IGN Aryawan Asasandi; Aeko FRF Utama; Fadli (Universitas Mataram, 2026)
This community service aims to: (1) Increase the capacity of financial management, bookkeeping and reporting of the UMKN group of gedongan weaving artisans in Pringgasela Village, Pringgasela District, East Lombok Regency; (2) Show the UMKN group of women who are members of gedongan weaving artisans about good and efficient marketing management techniques; and (3) Establish relationships between universities, especially the Faculty of Agriculture, University of Mataram, and the community. The method used in this community service is the community development method, which emphasizes adult learning by involving 30 members of the target group and 11 KKN students. The results of this community service activity indicate that: (1) the program was implemented well and smoothly. This was demonstrated by the active participation of the target group throughout the entire series of activities and the participants' ability to receive and understand the science and technology (ipteks) presented; (2) this community service activity was proven to improve the participants' knowledge and skills, particularly in aspects of business financial management, simple bookkeeping, preparation of group business reports, and marketing strategies for gedogan woven handicrafts; and (3) this activity also strengthened the partnership between universities, in this case the Faculty of Agriculture, University of Mataram, and the community.